Comparison of Responsiveness of British Isles Lupus Assessment Group 2004 Index, Systemic Lupus Erythematosus Disease Activity Index 2000, and British Isles Lupus Assessment Group 2004 Systems Tally. Issue 10 (10th June 2022) - Yee, Chee‐Seng; Gordon, Caroline; Isenberg, David A.; Griffiths, Bridget; Teh, Lee‐Suan; Bruce, Ian N.; Ahmad, Yasmeen; Rahman, Anisur; Prabu, Athiveeraramapandian; Akil, Mohammed; McHugh, Neil; Edwards, Christopher J.; et al.
Abstract : Objective: To compare the responsiveness of the British Isles Lupus Assessment Group 2004 index (BILAG‐2004) and the Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI‐2K) disease activity indices and to determine whether there was any added value in combining BILAG‐2004, BILAG‐2004 system tally (BST), or simplified BST (sBST) with SLEDAI‐2K. Methods: This was a multicenter longitudinal study of SLE patients. Data were collected on BILAG‐2004, SLEDAI‐2K, and therapy on consecutive assessments in routine practice. The external responsiveness of the indices was assessed by determining the relationship between change in disease activity and change in therapy between 2 consecutive visits. Comparison of indices and their derivatives was performed by assessing the main effects of the indices using logistic regression. Receiver operating characteristic curves analysis was used to describe the performance of these indices individually and in various combinations, and comparisons of area under the curve were performed. Results: There were 1, 414 observations from 347 patients. Both BILAG‐2004 and SLEDAI‐2K maintained an independent relationship with change in therapy when compared. There was some improvement in responsiveness when continuous SLEDAI‐2K variables (change in score and score of previous visit) were combined with BILAG‐2004 system scores. Dichotomization of BILAG‐2004 or SLEDAI‐2K resulted in poorer performance. BST and sBST had similar responsiveness as the combination of SLEDAI‐2K variables and BILAG‐2004 system scores. There was little benefit in combining SLEDAI‐2K with BST or sBST. Conclusion: The BILAG‐2004 index had comparable responsiveness to SLEDAI‐2K. There was some benefit in combining both indices. Dichotomization of BILAG‐2004 and SLEDAI‐2K leads to suboptimal performance. BST and sBST performed well on their own; sBST is recommended for its simplicity and clinical meaningfulness.